INFLUENCE OF CULEX FATIGANS AND GOAT LIVER AS FOOD ON FLESH PRODUCTION IN MACROPODUS CUPANUS - Manoharam, Joycy Jay (Indian Journal of Fisheries, 2011)
Chosing three different size groups of the fish Macropodus cupanus the flesh production fias been studied by providing goat liver and Ciilex futigims las food. Maximum flesh production was found in large-size fish when fed ad ibitum with Culex fatigans. There is a decrease in the rate of feeding, assimilation and conversion with an increase in the body weight of the fish. Fish cultured with goat liver as food displayed more assimilation efficiency than those fed on C. fatigans. Fish fed on C. fatigans. showed maximum specific growth and flesh production.